Adding the patient's voice to our understanding of collaborative goal setting: How do patients with diabetes define collaborative goal setting?. (December 2016) - Morris, Heather L; Carlyle, Kellie E; Elston Lafata, Jennifer
Background: Patient reports of collaborative goal setting have repeatedly been associated with improved health outcomes, and the American Diabetes Association specifically encourages collaborative goal setting as a component of high quality care. Current limitations in our understanding of what needs to transpire for patients to denote goal setting as "collaborative", remain a barrier to fostering collaborative goal setting in practice. Methods: Four focus groups were conducted among 19 patients with diabetes. A semi-structured focus group guide was used to explore patient perceptions of collaborative goal setting and what needed to happen for goals to be considered collaboratively set. Focus group transcripts were coded using thematic analysis. Results: Collaborative goal setting was described by patients as occurring within the context of a caring relationship where patients and health care providers: (1) listen and learn from each other; (2) share ideas; (3) agree on a measurable objective; and (4) support goal achievement. Patients also articulated clear responsibilities for themselves and clinicians and described collaborative goal setting as a process that occurs over time. Conclusions: Patients perceived collaborative goal setting as a multidimensional process that occurs over time within the context of a caring relationship and encompasses distinct patient and clinician responsibilities.